Development of CTL-Based Teaching Modules to Improve Learning Outcomes of Phase B Elementary Students - Kusumah, Dhea Aristi; Saputri, Aprilia Eki; Anasta, Non Dwishiera Cahya (Widyagogik, 2025)
This research was motivated by the low learning outcomes of phase B elementary school students in the IPAS subject, particularly on the water cycle topic. This study aims to develop a teaching module based on Contextual Teaching and Learning (CTL) to improve students' learning outcomes. The method used is Design and Development (DD) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The results show that the CTL-based teaching module is highly feasible to use, with an average validation score of 91.66%. Furthermore, the N-Gain test results indicate an improvement in students' learning outcomes with a score of 0.66, categorized as moderate. This study recommends using CTL-based teaching modules as an alternative approach to enhance understanding and learning outcomes in IPAS subjects.